Time, ignorance, and uncertainty in economic models - Katzner, Donald W. (Ann Arbor : University of Michigan Press, 1998)
Emerging from the tradition of Marshall, Knight, Keynes, and Shackle, "Time, Ignorance, and Uncertainty in Economic Models" is concerned with the character of formal economic analysis when the notions of logical or mechanical time and probabilistic uncertainty and the relatively complete knowledge basis it requires, are replaced, respectively, by historical time, and nonprobabilistic uncertainty and ignorance. Examining that analytical character by constructing and exploring particular models, this book emphasizes doing actual economic analysis in a framework of historical time, nonprobabilistic uncertainty, and ignorance.Donald W. Katzner begins with an extensive investigation of the distinction between potential surprise and probability. He presents a modified version of Shackle's model of decision-making in ignorance and examines in considerable detail its "comparative statics" and operationality properties. The meaning of aggregation and simultaneity under these conditions is also explored, and Shackle's model is applied to the construction of models of the consumer, the firm, microeconomics, and macroeconomics. Katzner concludes with discussions of the roles of history, hysteresis, and empirical investigation in economic inquiry."Time, Ignorance, and Uncertainty in Economic Models" will be of interest to economists and others engaged in the study of uncertainty, probability, aggregation, and simultaneity. Those interested in the microeconomics of consumer and firm behavior, general equilibrium, and macroeconomics will also benefit from this book.Donald W. Katzner is Professor of Economics, University of Massachusetts.
Includes bibliographical references and index.
lje 31/01/14 rua 21/04/15
Loans
Keywords: Economics; Ignorance (Theory of knowledge); Time and economic reactions; Information theory in economics; Uncertainty (Information theory)